The translocation of the transition of copper from a dark gray podzolized soil to winter wheat plants - Тогачинська, О. В.; Паращенко, І. В. (Scientific Progress & Innovations, 2018)
The research was carried out on the basis of the Institute of Agroecology of the UAAS and the NSC «Institute of Agriculture of UAAS». Winter wheat variety – Lada Odes’ka. The soil of the experimental field is dark gray podzolized. The scheme of the experiment involved the study of fertilizer variants against the background of the minimal and intensive system of plant protection: control (without fertilizers), N60N30, P135K135 + N80 + N55, by-products, P90K90 + N60 + N30. The results of ecological examination of technologies of winter wheat growing in the Northern Forest-Steppe for the influence on the processes of copper migration in the genetic horizons of dark gray podzolized soil and its accumulation in vegetative and generative organs of plants are highlighted. The results of ecotoxicological studies have revealed that the mineral fertilizer system and intensive plant protection can cause the accumulation of potentially hazardous substances in the upper horizons of the soil. As well as promote their migration down the soil profile and create a potential threat to groundwater contamination. It was established that under the influence of mineral fertilizers (P135K135 + N80 + N55, P90K90N60 + N30, N45P45K45) intensive protection was carried out more active accumulation of potentially dangerous substances by vegetative (stem, leaves) by the organs of wheat. The use of by-products led to a decrease in the activity of these processes. Fertilizer systems, and especially plant protection, have had a significant impact on the redistribution of harmful substances between vegetative and generative organs of wheat. The amount of copper in winter wheat grains with intensive plant protection increased significantly. Prospects for scientific work in the future will be aimed at studying the influence of the transition of the transition of nickel, zinc from the soil into vegetative and generative organs of winter wheat and conducting an environmental assessment of technologies for growing winter wheat according to toxicological indicators.